2021
DOI: 10.1016/j.coviro.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells and unconventional T cells in COVID-19

Abstract: NK cells and diverse populations of unconventional T cells, such as MAIT cells, γδ T cells, invariant NKT cells, and DNT ɑβ cells are important early effector lymphocytes. While some of these cells, such as NK cell and MAIT cells, have well-established roles in antiviral defense, the function of other populations remains more elusive. Here, we summarize and discuss current knowledge on NK cell and unconventional T cell responses to SARS-CoV-2 infection. Also covered is the role of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 70 publications
2
26
0
1
Order By: Relevance
“…Researchers found overexpression of interferon-related genes, and increased activation of NK cells and T cells (97)(98)(99). Also, it was found that there was an association between SARS-CoV-2 infection and local immune responses at the maternal-fetal interface (97).…”
Section: Biomarkers Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Researchers found overexpression of interferon-related genes, and increased activation of NK cells and T cells (97)(98)(99). Also, it was found that there was an association between SARS-CoV-2 infection and local immune responses at the maternal-fetal interface (97).…”
Section: Biomarkers Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Finally, CD56 dim CD16 neg NK cells are unconventional CD56 dim cells whose cytotoxic capacity has been found to be lower compared to that of CD56 dim CD16 pos NK cells [32,33]. In this regard, the downregulation of CD16 expression has been also described in Herpes and Varicella zoster infections and might be associated with abnormal NK cell maturation during infection or prolonged cellular activity/activation, driving CD16 shedding, which might be a regulatory mechanism to prevent activation-induced cell death [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…During infection, NKT cells migrate from the circulation to the lung, where they form aggregates. An increased concentration of highly activated NKTs is observed, following chemokine release in the bronchoalveolar lavage (BAL) of patients with COVID-19 [ 22 ]. NKT cells are important antiviral effectors due to their ability to respond without a prior sensitization, and therefore, are able to produce IL-17 immediately following antigen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…NKT cells are important antiviral effectors due to their ability to respond without a prior sensitization, and therefore, are able to produce IL-17 immediately following antigen exposure. In contrast, IL-17 production from CD4 + T cells is more complex, and depends on different factors and cytokines [ 6 , 21 , 22 ]. Likewise, γδ T cells have been characterized as a primary source of IL-17 secretion in several in vitro lung injury models [ 20 ].…”
Section: Discussionmentioning
confidence: 99%